2022
DOI: 10.1021/acsaelm.2c00065
|View full text |Cite
|
Sign up to set email alerts
|

Heating-Induced Performance Degradation of REBa2Cu3O7–x Coated Conductors: An Oxygen Out-Diffusion Scenario with Two Activation Energies

Abstract: The degradation of the superconducting properties of REBa 2 Cu 3 O 7−x coated conductors when heated above 150 °C is a topic of concern for any REBa 2 Cu 3 O 7−x -based applications. This study makes it clear the role of thermally activated oxygen out-diffusion processes in the modification of the superconducting properties of commercial coated conductors heat treated in air. We point out that oxygen can diffuse out of the REBa 2 Cu 3 O 7−x layer along two main channels: one associated with the grain boundarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…We assumed that a 5-7.5 mm long section in both wires, consistent with the burn-out, absorbed an equal amount of heat under an adiabatic condition. The estimated peak temperature during Ramps 11-19 ranged from 440 to 1040 K, high enough to degrade the critical current of rebco tapes [76,77]. A recent corc® dipole magnet suffered a similar critical-current degradation, possibly also due to the conductor heating [49].…”
Section: Continue Developing Star® Conductors Based On the Feedback F...mentioning
confidence: 99%
“…We assumed that a 5-7.5 mm long section in both wires, consistent with the burn-out, absorbed an equal amount of heat under an adiabatic condition. The estimated peak temperature during Ramps 11-19 ranged from 440 to 1040 K, high enough to degrade the critical current of rebco tapes [76,77]. A recent corc® dipole magnet suffered a similar critical-current degradation, possibly also due to the conductor heating [49].…”
Section: Continue Developing Star® Conductors Based On the Feedback F...mentioning
confidence: 99%
“…As oxygen continues to diffuse out of the REBCO, this ultimately results in a decrease in I c . The work by Bonura [5] suggests that below 250 • C, oxygen diffuses out of REBCO predominantly via grain boundaries, implying our results may also be grain boundary localized effects; in this case, it would be the loss of superconductivity in the grain boundaries rather than the grains that causes the ultimate decrease in I c in the Faraday samples, by reducing grain connectivity and possible current paths. Improved pinning due to oxygen vacancies or the variation in properties of some of these secondary grains which may act as current-blocking defects [17], remains a possibility.…”
Section: Sem Images Of the Rebco Layermentioning
confidence: 70%
“…The initial tape soldering process to manufacture the cable or coil involves significant heat application to the tapes which can result in thermal degradation [3]. Recent works [4,5] have also shown that individual HTS tapes degrade at temperatures even lower than the soldering temperature, via oxygen-out diffusion from the grain boundaries and grains of the REBCO layer. Post manufacturing, another application that involves heat cycling is the operation of a low temperature solder demountable joint to couple superconducting tape stacks, which avoids melting the Pb 37 Sn 63 , but requires elevated temperatures to mount and demount the joint [3].…”
Section: Introductionmentioning
confidence: 99%
“…To solder directly to aluminium, temperatures over 280 • C would be needed to remove the refractory oxide on the surface with reactive chloride fluxes [10]. Exposure to this temperature would permanently degrade the performance of the tapes [13,14]. Next to that, aluminium specific solders flow poorly, and aluminium reacts with Sn-Pb solders causing corrosion at the solder interface [10] leading to bad contact.…”
Section: Coating Of the Support Cylindermentioning
confidence: 99%